Impact of oral hygiene on the development of oropharyngeal neoplasms - D. G. Kiparisova; Yu. S. Kiparisov; N. S. Nurieva (Опухоли головы и шеи, 2015)
Objective. To evaluate the impact of oral hygiene on the development of oropharyngeal malignancies.Subjects and methods. The data of a prospective study of dental health indicators were analyzed in 586 patients (there were 76.4 % men and 23.6 % women) with oropharyngeal malignancies. In the examinees, the sites of oropharyngeal neoplasms were as follows: the tongue in 195 (33 %) cases, mouth floor in 147 (25 %), oropharynx in 139 (24 %), maxilla in 36 (6 %), buccal mucosa in 21 (4 %), soft palate in 18 (3 %), retromolar area in 14 (2 %), mandibula in 12 (2 %), and nose in 4 (1 %). The patients, examination employed routine dental examinations, determination of oral hygiene index, CFE index (a sum of carious, filled, and extracted teeth), and assessment of a patient, s skill and desire to perform individual oral hygiene. The patient hygiene performance (PHP) index (Podshadley, Haley, 1968) was used to estimate his/her baseline ability. The rates of initial visits made by patients with oropharyngeal tumors to physicians of different specialties were also analyzed.Results. In the patients with oropharyngeal malignancies, the CFE index was high and amounted to 15 ± 0.4 с with a preponderance of carious and extracted teeth in the pattern; the PHP index was 1.4 ± 0.1, which corresponded to a satisfactory index. Thus, among the comparison group patients, satisfactory oral cavity sanitation was noted in only 4.8 % of the patients having a sanitation certificate. Consequently, 95.2 % of the patients were unready for specialized treatment. Out of the examinees, 176 (30 %) made an initial visit for complaints to a dentist, 155 (26.5 %) to an oncologist, 107 (18.3 %) to an ENT doctor, 103 (17.7 %) to a local therapist, and 43 (7.5 %) to a surgeon. The collected history data also revealed that 59.2 % of the patients had self-treatment before going to specialists (according to them). Self-treatment or treatment by a noncancer specialist was ascertained to take an average of 1 to 3 months, 4 to 6 months, and 6 months to 1 year in 52.4 %, 28.6 % and 19 %, respectively. This factor is responsible for the visits made by patients with stages III–IV cancer to oncology facilities.Conclusion. It is concluded that the level of oral hygiene practices is low; the state of oral organs and tissues is generally unsatisfactory in the patients with oropharyngeal neoplasms; their dental visits are irregular, and they had mainly self-treatment. Irregular dental visits for oral prophylaxis and an untimely dental search for oral problems lead to the fact that the patients of this category are hospitalized to a specialized institution when they have mainly stages III–IV cancer, which accordingly determines further specialized treatment policy and long-term prognoses. The dentist should make a significant contribution to the diagnosis of maxillofacial malignancies.